Hydroxytyrosol Recovers SARS-CoV-2-PLpro-Dependent Impairment of Interferon Related Genes in Polarized Human Airway, Intestinal and Liver Epithelial Cells - Annalisa Crudele; Antonella Smeriglio; Mariarosaria Ingegneri; Nadia Panera; Marzia Bianchi; Maria Rita Braghini; Anna Pastore; Valeria Tocco; Rita Carsetti; Salvatore Zaffina; Anna Alisi; Domenico Trombetta (MDPI AG, 2022)
The SARS-CoV-2 pandemic has caused approximately 6.3 million deaths, mainly due to the acute respiratory distress syndrome or multi-organ failure that characterizes COVID-19 acute disease. Post-acute COVID-19 syndrome, also known as long-COVID, is a condition characterized by a complex of symptoms that affects 10-20% of the individuals who have recovered from the infection. Scientific and clinical evidence demonstrates that long-COVID can develop in both adults and children. It has been hypothesized that multi-organ effects of long-COVID could be associated with the persistence of virus RNA/proteins in host cells, but the real mechanism remains to be elucidated. Therefore, we sought to determine the effects of the exogenous expression of the papain-like protease (PLpro) domain of the non-structural protein (NSP3) of SARS-CoV-2 in polarized human airway (Calu-3), intestinal (Caco-2), and liver (HepG2) epithelial cells, and to evaluate the ability of the natural antioxidant hydroxytyrosol (HXT) in neutralizing these effects. Our results demonstrated that PLpro was able to induce a cascade of inflammatory genes and proteins (mainly associated with the interferon pathway) and increase the apoptotic rate and expression of several oxidative stress markers in all evaluated epithelial cells. Noteably, the treatment with 10 μM HXT reverted PL-pro-dependent effects almost completely. This study provides the first evidence that SARS-CoV-2 PLpro remaining in host cells after viral clearance may contribute to the pathogenetic mechanisms of long-COVID. These effects may be counteracted by natural antioxidants. Further clinical and experimental studies are necessary to confirm this hypothesis.